2020
DOI: 10.1186/s12889-020-08523-w
|View full text |Cite
|
Sign up to set email alerts
|

Child and adolescent injury burden in the eastern mediterranean region: Findings from the Global Burden of Disease 1990-2017

Abstract: Background: Child and adolescent injury is one of the leading causes of child death globally with a large proportion occurring in Low-and Middle-Income Countries (LMICs). Similarly, the Eastern Mediterranean Region (EMR) countries borne a heavy burden that largely impact child and adolescent safety and health in the region. We aim to assess child and adolescent injury morbidity and mortality and estimate its burden in the Eastern Mediterranean Region based on findings from the Global Burden of Disease (GBD), I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…These estimates signal an alarming indicator of the MVA burden across regional MENA countries. This finding is consistent with existing evidence that underscores the high burden of MVA in the region [73], possibly explained by the rapid urbanization of many MENA countries along with major changes in the automobile industry and coupled with lax government-enforced safety regulations that resulted in the increased frequency and severity of MVAs.…”
Section: Discussionsupporting
confidence: 91%
“…These estimates signal an alarming indicator of the MVA burden across regional MENA countries. This finding is consistent with existing evidence that underscores the high burden of MVA in the region [73], possibly explained by the rapid urbanization of many MENA countries along with major changes in the automobile industry and coupled with lax government-enforced safety regulations that resulted in the increased frequency and severity of MVAs.…”
Section: Discussionsupporting
confidence: 91%
“…There is an evidence that in the EMRO, the number of deaths due to IPV has more increased in recent years compared to rest of the world due to the recent widespread con icts in this region (39). Findings of a systematic review in the EMRO showed that although the mortality rate in people aged 0-19 years due to "RTI" and "other unintentional injuries" decreased during the years 1990 to 2017, mortality due to "SH and IPV" increased in this age group and tripled during this period (40). The results of a study by Patton et al, which examined the global pattern of mortality in young people, also showed that SH and suicide were increased in young men and women and was the second most common cause of death in this age (8).…”
Section: Discussionmentioning
confidence: 99%
“…The burden of childhood injury is disproportionally distributed between developing and developed countries with the majority of child injuryrelated mortality and morbidity occurring in low-and middle-income countries [4]. Several Middle Eastern studies had underscored the gravity and the increased burden of childhood injuries in the region [5][6][7][8]. Compared to its neighboring countries, Lebanon sustains even a larger burden of childhood injuries.…”
Section: Introductionmentioning
confidence: 99%